2007
DOI: 10.1088/0954-3899/34/3/002
|View full text |Cite
|
Sign up to set email alerts
|

Indication for π+π scattering in p + p collisions at GeV

Abstract: A ρ(770) 0 mass shift of about -40 MeV/c 2 was measured in p+p collisions at √ s N N = 200 GeV at RHIC. Previous mass shifts have been observed at CERN-LEBC-EHS and CERN-LEP. We will show that phase space does not account for the ρ(770) 0 mass shift measured at RHIC, CERN-LEBC-EHS and CERN-LEP and conclude that there are significant scattering interactions in p + p collisions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…All these explanations require an interaction, which implies a medium such as the one formed in A+A collisions. However, the ρ 0 mass shift measured in p+p collisions [3] can be described without a medium [35]. The ++ width and the * mass and width measured are in agreement with previous measurements [26].…”
Section: E Nuclear Modification Factorsupporting
confidence: 89%
See 2 more Smart Citations
“…All these explanations require an interaction, which implies a medium such as the one formed in A+A collisions. However, the ρ 0 mass shift measured in p+p collisions [3] can be described without a medium [35]. The ++ width and the * mass and width measured are in agreement with previous measurements [26].…”
Section: E Nuclear Modification Factorsupporting
confidence: 89%
“…Dynamical interactions with the surrounding matter, interference between various π + π − scattering channels, phase-space distortions due to the rescattering of pions forming ρ 0 , and Bose-Einstein correlations between ρ 0 decay daughters and pions in the surrounding matter were previously given as the possible explanations [3]. It has been proposed [35] that the mass shift observed in p+p collisions is due to ππ rescattering, which requires no medium. Since one also does not expect a medium to be formed in d+Au collisions, if dynamical interactions are also the explanation for the mass shift, then the rescattering of the ρ 0 with the surrounding particles must exist.…”
Section: A Masses and Widthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several explanations have been offered for the observed mass shift of the Δ ++ in d+Au, including dynamical interactions with the surrounding matter, distortions of the phase space due to re-scattering of the daughters, and Bose-Einstein correlations with pions in the surrounding matter [3]. For the mass shift observed in p + p it has been suggested that ππ re-scattering may be responsible since it does not require the presence of a medium [9]. Residual background in the case of the Σ(1385) comes mostly from the Ξ and Ξ, which have the same decay channels as the Σ(1385) and Σ(1385).…”
Section: Masses and Widthsmentioning
confidence: 99%
“…Since we are projecting in p t this weighting will be an exponential function of the transverse mass divided by the temperature [6,[9][10][11][12][13].…”
Section: Thermal Production Of Resonancesmentioning
confidence: 99%